’n Postmoderne beskouing oor die teologiese legitimering van apartheid met verwysing na die veertigerjare van die vorige eeu - Brits, HJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
The history of apartheid shows how difficult it is to depart from a dominant discourse. In seeking the will of God for its people and for society, the Afrikaner church legitimised the apartheid ideology with the historic “opening of the apartheid bible” by Totius. This article reflects from a social constructivist point of view on the role of prominent Afrikaners and theologians in legitimising apartheid in the nineteen forties.